Low-Noise Amplifier Design For Polar Weather Satellite Receiver - R.Subramani, Hariharan (Universiti Sains Malaysia, 2006)
For undergraduate program, a low-noise amplifier for satellite communication system was designed. This low-noise amplifier would play the role as a front end of a satellite receiver that operates in the UHF band. The low-noise amplifier would perform amplification with reasonable gain on the weak signal received from the satellite while maintaining a low noise figure. The amplified signal would then be passed on to the succeeding stages. The design of the amplifier commences with the selection of the discrete components that will be used. After making the suitable passive and active component selection, the chosen microwave transistor model is then simulated in Advanced Design System (ADS2005A) to get the scattering parameters and stability figure. After impedance matching is done, the printed circuit board is designed with the same software. Finally, the resulting actual circuit performance are recorded down and then compared with the results obtained from simulation. The fabricated low-noise amplifier showed that choosing the right passive components and proper printed circuit board design plays an important role in ensuring that the fabricated circuit specification closely resembles the simulated counterpart. The measurement of IP3, OIP3, noise figure, gain and gain compression point (P1dB) utilizing the network analyzer, noise source and spectrum analyzer are also presented here.